Early weaning among infants in Philanthropic Hospital in Aracaju - Araujo, Naiana Mota (2021)
The objective of the present study is to assess the most prevalent causes of early weaning in infants attended in Pediatric Emergency at the Philanthropic Hospital from January to April 2019 and to encourage the help of health professionals, so maternal difficulties in relation to breastfeeding can be resolved. It is a cross-sectional, analytical study, based on data collected from questionnaires formulated through relevant information sourced from high-quality published research, to the mothers of infants aged 0 to 12 months who were being treated at the pediatric urgent care. Was spotted that exclusive breastfeeding in infants under 6 months was 35,6% (n = 26), while predominant breastfeeding was 15,1% (n = 11). The average period of time during which the infants had been exclusively breastfed was 2 months. With respect to early weaning, 51% (n = 46) of mothers reported milk being weak or low in quantity as the reason; 14% (n = 13) attributed it to their professional careers and 14% (n = 13) reported a loss of interest by the infant. In view of this research, it was concluded found that the main reasons for early weaning are related to the quantity and quality of breast milk, followed by returning to work and the infant losing interest in breastfeeding.